Detection of Parkinson’s disease from Neuro-imagery using deep neural network with transfer learning - Asaduzzaman; Sakib, A.F.M. Nazmus; Shusmita, Sanjida Ali; Kabir, S. M. Ashraf (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.